Effects of Controlled-release Bulk Blending Fertilizer on Wheat Yield of Different Varieties under Various Soil Basic Fertility. Issue 1 (31st December 2022) - Lu, Hao; Wang, Rui; Dun, Canping; Wang, Di; Zhang, Haipeng; Cui, Peiyuan; Dai, Qigen; Zhang, Hongcheng
ABSTRACT: In order to explore a fertilization scheme that can adapt to different soil fertility conditions and wheat varieties, two kinds of controlled-release ureas with different release periods (60 days (CRU-60 d) and 90 days (CRU-90 d)) blending with ordinary urea were applied in different proportions at three different sites to evaluate the impacts of controlled-release bulk blending fertilizer (CRBBF) on soil NO3 – N, NH4 + -N contents and dynamic change of tillers, SPAD value, grain yield and yield components. The results indicated that applying CRBBF could increase soil NO3 – N, NH4 + -N contents, tiller numbers, leaf areas, leaf SPAD values and grain yield. Compared with local farmers' habitual fertilization treatment, CRBBF application presented a higher soil inorganic N content, yield with more spikes and grains per spike. This study has important guiding significance for one-time fertilization of wheat and provides an effective way to alleviate the non-point source pollution caused by excessive fertilization.